2019
DOI: 10.3892/mmr.2019.10182
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet lysate as an alternative to fetal bovine serum for culture and endothelial differentiation of human amniotic fluid mesenchymal stem cells

Abstract: Human amniotic fluid (hAF) mesenchymal stem cells (MSCs) are commonly cultured in medium containing FBS. However, there are concerns about using animal serum in therapeutic applications due to the potential for immunogenic reactions and the risk of transmission of pathogens. For safety reasons, human platelet lysate (hPL) has been suggested as a replacement for FBS because it appears to be a natural source of growth factors. In this present study, it was investigated whether FBS could be substituted with hPL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
4
8
0
Order By: Relevance
“…Each GelMA solution was prepared in PBS with the addition of 0%, 2.5%, or 50% hPL (% v/v) or by adding hPL only (100% hPL), prior to the addition of the photoinitiator and the polymerization of the hydrogels. The specific hPL concentrations used in this study were selected because: (1) 2.5% hPL is the recommended concentration for 2D cell cultivation [33,34]; (2) 100% represents a complete substitution of PBS with hPL; (3) 50% hPL serves as an intermediate point between 2.5% and 100% hPL; and (4) 0% hPL functions as a control. Calcein-AM staining was performed to evaluate the influence of hPL addition on cell viability and spreading.…”
Section: Resultsmentioning
confidence: 99%
“…Each GelMA solution was prepared in PBS with the addition of 0%, 2.5%, or 50% hPL (% v/v) or by adding hPL only (100% hPL), prior to the addition of the photoinitiator and the polymerization of the hydrogels. The specific hPL concentrations used in this study were selected because: (1) 2.5% hPL is the recommended concentration for 2D cell cultivation [33,34]; (2) 100% represents a complete substitution of PBS with hPL; (3) 50% hPL serves as an intermediate point between 2.5% and 100% hPL; and (4) 0% hPL functions as a control. Calcein-AM staining was performed to evaluate the influence of hPL addition on cell viability and spreading.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, low PL doses have been used (2.6 ÎĽg of total protein/cm 2 , namely 0.02 ml of PL per 100 ml in the cell culture media in combination with a 1% EV-depleted FBS) while 10% of PL is normally used in substitution of FBS for MSC maintenance. 45 Further studies should be performed to evaluate the dose-effect response of PL and affirm the potential to use it as a FBS xeno-free substitute.…”
Section: Discussionmentioning
confidence: 99%
“…In particular Kandoi et al evidenced significantly faster cell growth of umbilical cord tissue-derived MSC in hPL-enriched cultures, reaching PDT of 20.95 h vs. PDT in FBS [ 5 ]. In contrast, Tancharoen et al revealed that amniotic fluid-derived MSC cultured in 10% FBS or hPL did not show differences in cell number and shared a fibroblast-like morphology [ 34 ]. In that regard, cell morphology has evolved as critical parameter predicting the expansion response to a particular cell supplement.…”
Section: Discussionmentioning
confidence: 99%